Mitigating emissions from pig and poultry housing facilities through air scrubbers and biofilters: State-of-the-art and perspectives. (June 2015) - Van der Heyden, Caroline; Demeyer, Peter; Volcke, Eveline I.P.
Abstract : The global intensification of livestock production resulted in potentially higher emissions of ammonia, odour, particulate matter (PM) and greenhouse gases (nitrous oxide and methane). Air scrubbers and biofilters were introduced as a low ammonia emission housing technique. However, regulations with regard to the use of air scrubbers changed, including also removal efficiencies for odour and PM besides ammonia. In practice however, the required removal efficiencies for these pollutants are not always obtained, indicating the need of process optimisation in terms of process design and/or operation. When optimising air scrubbers, it is argued and recommended to anticipate the growing attention towards greenhouse gases, such as methane and nitrous oxide, which are present in exhaust air from animal housing facilities. However up till now, very little is known about the behaviour of greenhouse gases in air scrubbers and biofilters. Moreover, the formation of nitrous oxide in (biological) air scrubbing systems cannot be excluded. This contribution summarises the state-of-the-art of air scrubbers and biofilters for the reduction of emissions of ammonia, odour, nitrous oxide, methane and fine dust and points out perspectives for process optimisation in terms of design and control. The air and liquid flow configuration, packing dimensions and packing material should be carefully considered. Control options for water flow rate, water discharge and acid dosage need to be optimised. Dosage of apolar solvents and inoculation of the packing material can be innovative control options to achieve a better removal of less water-soluble components. Highlights: Exhaust air from pig and poultry housing facilities was characterised. Removal of NH3, odour, N2 O, CH4 and PM in air scrubbers and biofilters is reviewed. Air/liquid flow configuration and packing size/material are important design aspects. Water flow rate, water discharge and acid dosage require adequate control strategies. Removal of low solubility components such as odour and methane could be optimised.